Comparative and Differential Study of Passiflora incarnata L. and Passiflora caerulea L. in Raw Plants and Pharmaceutical Dosage Forms - H Hajimehdipoor; Sh Rezazadeh; A Hadjiakhoondi; M Pirali Hamedani; A Rezaee; H Zahedi; N Kalantari Khandani (Institue of Medicinal Plants, ACECR, 2007)
Background: Passiflora has several species that two of them named P. incarnata and P. caerulea are cultivated in Iran. Many investigations have been carried out on therapeutic effects of the genus but only P. incarnata is approved for use in pharmaceutical dosage forms for anxiety and insomnia. Objective: The purpose of this study is differential determination of P. incarnata and P. caerulea in medicinal plants and related herbal drugs. Method: In this investigation, microscopic properties, total ash, acid-insoluble ash and total flavonoids calculated as hyperoside of P. incarnata and P. caerulea were determined. In addition, TLC chromatogram regarding flavonoids and HPLC chromatograms of P. incarnata and P. caerulea ethanol extract, Passipay tablet and drop (Iran Darouk Co.), Passiflora drop and dry extract (Vogel Co.) and Passiflora drop (Curarina Co.) were also compared. Results: No significant difference between total ash, acid-insoluble ash and total flavonoids in two species were found. But they were very different in microscopic properties. TLC and HPLC chromatograms are very different as well. Conclusion: The aerial parts of the two plant species can be well distinguished by microscopic method. The plant extract either itself or in pharmaceutical dosage forms, can be determined by HPLC or TLC methods. Since sample preparation is very simple and doesn't require complex procedures, the above-mentioned methods seem to be efficient.